2018
DOI: 10.1007/s10811-018-1641-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel species of the oomycete Olpidiopsis potentially threaten European red algal cultivation

Abstract: The rapid growth of marine macroalgal cultivation amplifies the potential impacts of seaweed diseases. Here, we combine microscopy and molecular analysis to describe two novel European species, Olpidiopsis palmariae and O. muelleri spp. nov., that infect the commercially important red algae Palmaria and Porphyra, respectively. A Scottish variety of Olpidiopsis porphyrae, a devastating pathogen of Pyropia previously thought to be restricted to Japanese seaweed farms, is also described as O. porphyrae var.scotia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…The introduction of new species to combat the loss of vigour and the transportation of live seedlings or seed stock is often practiced to support the development of seaweed aquaculture (Bindu and Levine 2011;Valderrama et al 2015;Hayashi et al 2017;Hwang et al 2018;Hurtado et al 2019). However, these practices are well documented as major pathways for introducing and facilitating the spread of diseases and pests in seaweed aquaculture worldwide (Sulu et al 2004;Largo et al 2017;Loureiro et al 2017;Badis et al 2019;Ward et al 2019). For example, the documented infection of Porphyra/Pyropia in Europe and Asia with the pathogenic oomycete Olpidiopsis (Kim et al 2014;Badis et al 2019;Ward et al 2019) and outbreaks of the epiphytic pests Neosiphonia and Polysiphonia spp.…”
Section: And New Regulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The introduction of new species to combat the loss of vigour and the transportation of live seedlings or seed stock is often practiced to support the development of seaweed aquaculture (Bindu and Levine 2011;Valderrama et al 2015;Hayashi et al 2017;Hwang et al 2018;Hurtado et al 2019). However, these practices are well documented as major pathways for introducing and facilitating the spread of diseases and pests in seaweed aquaculture worldwide (Sulu et al 2004;Largo et al 2017;Loureiro et al 2017;Badis et al 2019;Ward et al 2019). For example, the documented infection of Porphyra/Pyropia in Europe and Asia with the pathogenic oomycete Olpidiopsis (Kim et al 2014;Badis et al 2019;Ward et al 2019) and outbreaks of the epiphytic pests Neosiphonia and Polysiphonia spp.…”
Section: And New Regulationsmentioning
confidence: 99%
“…However, these practices are well documented as major pathways for introducing and facilitating the spread of diseases and pests in seaweed aquaculture worldwide (Sulu et al 2004;Largo et al 2017;Loureiro et al 2017;Badis et al 2019;Ward et al 2019). For example, the documented infection of Porphyra/Pyropia in Europe and Asia with the pathogenic oomycete Olpidiopsis (Kim et al 2014;Badis et al 2019;Ward et al 2019) and outbreaks of the epiphytic pests Neosiphonia and Polysiphonia spp. in Kappaphycus seedlings are both attributed to trading as a pathway for pest introductions (Hurtado et al 2019).…”
Section: And New Regulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these parasitoids are known to play a significant role in breaking down blooms of their host diatoms, and might also play a role in the marine food web (Skovgaard 2014;Scholz et al 2015). So far, only three marine oomycetes-infecting diatoms (Lagenisma coscinodisci, Diatomophthora drebesii and Miracula helgolandica) have been classified and studied for molecular phylogeny (Thines et al 2015;Buaya et al 2017), but additional lineages have been identified that have not been formally described (Badis et al 2019;Garvetto et al 2018Garvetto et al , 2020. The Coscinodiscophyceae parasitoid L. coscinodisci was found to belong to the basal Saprolegniomycetes (Thines et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetically, Anisolpidium is closely related to marine species of Olpidiopsis , and recently described clades of diatom pathogens named OOM_1 and OOM_2 (Garvetto et al , ). Olpidiopsis is a cosmopolitan genus that encompasses devastating pathogens of red algae, including laver, the most valuable seaweed crop in the world (Klochkova et al , ; Badis et al , ); the OOM_1 and OOM_2 clades contain pathogens potentially relevant to the control of phytoplankton dynamics and consequently, biogeochemical cycling. Finally, the early‐diverging position of Anisolpidium among oomycetes (Gachon et al , ) makes it an ideal model to address the physiology and evolutionary origin of pathogenicity and biotrophy in oomycetes.…”
Section: Introductionmentioning
confidence: 99%